Information About the Optimism of a Placebo/Nocebo Provider and Placebo/Nocebo Side Effects - Schlintl, Carina; Schienle, Anne (Frontiers in Psychology, 2021)
Background. Research has demonstrated that personality characteristics, such as optimism are associated with placebo/nocebo responding. The present study investigated whether written information about the optimism of a placebo/nocebo provider can influence the occurrence of reported placebo/nocebo side effects. Method. We analyzed data from 201 females (mean age = 26 years) who participated in a ‘clinical study on a new massage oil with stone clover extract’. The oil (sunflower oil) was introduced as either eliciting a negative side effect (unpleasant itching; ‘nocebo oil’) or a positive side effect (pleasant tingling; ‘placebo oil’). The administration of the oil was combined with written information about the maker of the product. The oil maker was either portrayed as a very optimistic person or no personal information was provided (only the company name). The participants had no personal contact with the experimenter and received all materials and instructions per post. Results. The participants reported more frequent and intense itching when they received a nocebo suggestion compared to a placebo suggestion. Positive tingling sensations were reported more frequently than itching but did not differ between the placebo/nocebo conditions. Information about the optimism of the oil maker was associated with a lower frequency of reported side effects (adverse and beneficial). Conclusion. This study demonstrated that it is sufficient to provide participants with written information about an inert substance to elicit the suggested side effect. Information about the provider’s optimistic personality did not specifically influence reported side effects. Future studies should focus on how to adapt written information about a drug/product to minimize adverse side effects and to maximize positive side effects.